2012
DOI: 10.1152/japplphysiol.00335.2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyperthermic hyperventilation during passive heating and prolonged light and moderate exercise in the heat

Abstract: Elevation of core temperature leads to increases in ventilation in both resting subjects and those engaged in prolonged exercise. We compared the characteristics of the hyperthermic hyperventilation elicited during passive heating at rest and during prolonged moderate and light exercise. Twelve healthy men performed three trials: a rest trial in which subjects were passively heated using hot-water immersion (41°C) and a water-perfused suit and two exercise trials in which subjects exercised at 25% (light) or 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 52 publications
(111 reference statements)
1
48
0
Order By: Relevance
“…However, there are several ways in which the increases in ventilation seen in resting subjects differ from those seen during exercise. At rest, ventilation does not increase until esophageal temperature (Tes) exceeds 38.0-38.5 °C [4][5][6] . Above this Tes threshold, minute ventilation (V ・ E), tidal volume and respiratory frequency all increase linearly in proportion to the increase in Tes 5,6) .…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there are several ways in which the increases in ventilation seen in resting subjects differ from those seen during exercise. At rest, ventilation does not increase until esophageal temperature (Tes) exceeds 38.0-38.5 °C [4][5][6] . Above this Tes threshold, minute ventilation (V ・ E), tidal volume and respiratory frequency all increase linearly in proportion to the increase in Tes 5,6) .…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%
“…At rest, ventilation does not increase until esophageal temperature (Tes) exceeds 38.0-38.5 °C [4][5][6] . Above this Tes threshold, minute ventilation (V ・ E), tidal volume and respiratory frequency all increase linearly in proportion to the increase in Tes 5,6) . On the other hand, White and Cabanac 7) reported that during incremental exercise, there is a core temperature threshold for hyperventilation around a tympanic temperature of 37.0-37.7 °C or a Tes of 37.5-37.9 °C, while Beaudin et al 8) and Sancheti and White 9) reported the Tes threshold for hyperventilation during incremental exercise to be around 37.1-38.2 °C.…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%
See 3 more Smart Citations